Exploring Rural/Remote Service Responses to Mistreatment of Older Aboriginal People - Pitts, Hannah; Blundell, Barbara; Gillieatt, Sue (2024)
The prevalence of mistreatment of older First Nations people has been estimated to be disproportionately high in comparison with the non-Indigenous population. This can be explained through an ecological framework as the impact of a complex interplay of individual, relational, community and societal factors. These factors include the intergenerational impacts of Australia’s colonial history on Indigenous Australians, entailing the disruption of families through child removal policies, land and cultural dislocation, and the severe violence, abuse and trauma to Aboriginal people that accompanied colonisation. Literature from various urban and regional Australian contexts has indicated the need for further research into the mistreatment of older First Nations people to inform service responses. Whilst this is already an under-researched area, there is even less literature within the specific context of rural and remote Australia. Barriers to service access in rural and remote Australian regions include geographical isolation and unsuitable urban-centric models of service provision. Further, Aboriginal communities in different geographical locations are highly diverse, making previous research difficult to generalise, as service responses to mistreatment need to be locally driven and locally responsive.